OsFBN6 Enhances Brown Spot Disease Resistance in Rice - Fang-Yuan Cao; Yuting Zeng; Ah-Rim Lee; Backki Kim; Dongryung Lee; Sun-Tae Kim; Soon-Wook Kwon (Plants)
Brown spot (BS) is caused by necrotrophs fungi Cochliobolus miyabeanus (C. miyabeanus) which affects rainfed and upland production in rice, resulting in significant losses in yield and grain quality. Here, we explored the meJA treatment that leads to rice resistance to BS. Fibrillins (FBNs) family are constituents of plastoglobules in chloroplast response to biotic and abiotic stress, many research revealed that OsFBN1 and OsFBN5 are not only associated with the rice against disease but also with the JA pathway. The function of FBN6 was only researched in the Arabidopsis. We revealed gene expression levels of OsFBN1, OsFBN5, OsFBN6 and the JA pathway synthesis first specific enzyme OsAOS2 following infection with C. miyabeanus, OsAOS2 gene expression showed great regulation after C. miyabeanus and meJA treatment, indicating JA pathway response to BS resistance in rice. Three FBN gene expressions showed different significantly regulated modes in C. miyabeanus and meJA treatment. The haplotype analysis results showed OsFBN1 and OsFBN5 the diverse Haps significant with BS infection score, and the OsFBN6 showed stronger significance (**** p < 0.0001). Hence, we constructed OsFBN6 overexpression lines, which showed more resistance to BS compared to the wild type, revealing OsFBN6 positively regulated rice resistance to BS. We developed OsFBN6 genetic markers by haplotype analysis from 130 rice varieties according to whole-genome sequencing results, haplotype analysis, and marker development to facilitate the screening of BS-resistant varieties in rice breeding. The Caps marker developed by Chr4_30690229 can be directly applied to the breeding application of screening rice BS-resistant varieties.